Cutaneous leishmaniasis caused by Leishmania infantum transmitted by Phlebotomus tobbi - Svobodová, Milena; Alten, Bulent; Zídková, Lenka; Dvorák, Vít; Hlavacková, Jitka; Mysková, Jitka; Seblová, Veronika; Kasap, Ozge Erisoz; Belen, Asli; Votýpka, Jan; Volf, Petr (International journal for parasitology, 2009)
Transmission of cutaneous leishmaniasis (CL) caused by Leishmania infantum was studied in South Anatolia, Turkey. Small, non-ulcerating lesions prevailed and patients were negative in rK39 tests for antibody detection for human visceral leishmaniasis (VL). The most abundant sand fly species, Phlebotomus tobbi, was found positive for Leishmania promastigotes with a prevalence of 1.4% (13 out of 898 dissected females). The isolated strains were identical with those obtained from patients with CL and were typed as L. infantum. Phylogenetic analysis revealed similarity to MON-188 and a clear difference from the MON-1 clade. Blood-meal identification showed that P. tobbi feeds preferentially on cattle and humans. This finding, the high number of CL patients and relative scarcity of dogs in the focus, suggests that the transmission cycle could be anthroponotic.
Keywords: Humans; lidé středního věku; dítě; Molecular Sequence Data; Child; Insect Vectors; molekulární sekvence - údaje; Phlebotomus; Female; dospělí; leishmanióza kožní; lidé; zvířata; Turecko; předškolní dítě; Adult; Cattle; ženské pohlaví; Leishmaniasis, Cutaneous; hmyz - vektory; Male; Middle Aged; Adolescent; skot; Turkey; leishmanióza viscerální; Leishmania infantum; Animals; Leishmaniasis, Visceral; mužské pohlaví; Child, Preschool; mladiství